A systematic review and data synthesis of longitudinal changes in white matter integrity after mild traumatic brain injury assessed by diffusion tensor imaging in adults. Issue 147 (February 2022) - Kim, Eunkyung; Yoo, Roh-Eul; Seong, Min Yong; Oh, Byung-Mo
Highlights: This study reviews longitudinal changes in white matter integrity after concussion. Longitudinal changes in diffusion metrics after concussion are highly heterogeneous. Many studies reported reduced fractional anisotropy (FA) regardless of injury phase. Early elevated FA can be normalized afterward and associated with good outcome. Abstract: Purpose: This study aimed to review diffusion tensor imaging studies of mild traumatic brain injury (mTBI) in adults with longitudinal acquisition of data and investigate the variability of findings in association with related factors, such as the time post-injury. Methods: Eligible studies from PubMed and EMBASE were searched to identify relevant studies for review. Of the 540 studies, 23 observational studies without intervention and with the following characteristics were included: original research in which adults with mTBI were examined, diffusion tensor imaging was acquired at least twice, white matter integrity was investigated by estimating diffusion metrics, and mode of injury was not restricted to sport- or blast-related mTBI. Results: Baseline scans were acquired within 3 weeks post-injury, followed by longitudinal scans within 3 months and at 12 months post-injury. During the acute/subacute period, mixed results (increase, decrease, or no significant change) of fractional anisotropy (FA) were observed compared to those in controls. Some studies reported increased FA during the acute/subacute period compared to controls, followed by normalization of FA. Decreased FA was also reported during the acute/subacute period, which lasted long into the chronic phase. In the acute phase, the mean diffusivity (MD) was greater than that in the controls. Compared to the early phase of injury, MD was reduced in the follow-up phase in most studies in the mTBI group. Insignificant differences in FA and MD have been reported in several studies. Such variability limits the clinical usefulness of diffusion tensor metrics. Conclusions: There was a high variability in reported changes in white matter integrity. Decreased FA not only in acute/subacute but also in long-term period after injury may indicate long-term neurodegenerative processes after mTBI. Nevertheless, longitudinal changes in MD towards normalization suggest possible recovery. Long-term cohort studies with research initiatives should be considered to elucidate brain changes after mTBI.